Linguistic and Paralinguistic Features of Speech Anxiety of High School Students - Ashriyyah, Aisyah Nur; Indah, Rohmani Nur (LPPM Universitas Bina Sarana Informatika, 2024)
This study analyzes the linguistic and paralinguistic features used by students who experience English-speaking anxiety in front of the Islamic Senior High School of Al–Karimi Gresik class. Speaking anxiety makes students afraid to express themselves because they feel incompetent and afraid of making mistakes. The study aimed to discover the linguistic and paralinguistic features shown when students are anxious about speaking. A qualitative method was used with data from voice recorder transcripts and notes. Further data collection was carried out using questionnaires to determine each participant's anxiety level. The findings show that code-mixing is the linguistic feature that most students exhibit. They constantly switch languages to Javanese or Indonesian when they experience anxiety due to vocabulary limitations. Meanwhile, pausing in the middle of sentences is the most exhibited paralinguistic feature. Based on the findings, it is recommended that English class students increase their vocabulary to reduce the possibility of language switching. In addition, teachers can ask students to prepare visuals and prompts to eliminate pauses and boost fluency.